The first EANS vascular and skull base hands-on course in East Africa: Review from the global and humanitarian neurosurgical committee initiative - Cadieux, Magalie; Demetriades, Andreas K; Rasulic, Lukas; Rutabasibwa, Nicephorus; Kinghomella, Alpha; Kaale, Aingaya; Yonah, Boaz; Preuss-Hernández, Christian; Härtl, Roger; Marchesini, Nicolò; Tisell, Magnus; Petr, Ondra (Brain & spine, 2025)
INTRODUCTION: Cerebrovascular pathologies in East Africa have a poorly known prevalence and incidence. The treatment remains sparse. When they apply, microneurosurgical techniques are prioritized over endovascular procedures due to lack of resources. Considering an increasing number of neurosurgeons in East Africa, the EANS Global Humanitarian Committee (GHC) has endorsed the creation of the Vascular and Skull base Hands-on Neurosurgery Course. RESEARCH QUESTION: What are essential elements to extend knowledge to sub-Suharan neurosurgeons on cerebrovascular pathologies? MATERIAL AND METHODS: In November 2023 was held the first course in collaboration with the Muhimbili Orthopaedic Institute (MOI) in Dar es Salaam, Tanzania. The course consisted of lectures from international and local faculty in the morning with surgical cases in the afternoon. Plus/delta type of feedback was obtained at the end. Challenges and proposed improvement based on comments are reported. RESULTS: The course lasted over five days and each day had a different theme of neurovascular or skull base neurosurgery. There was a total of 32 presenting faculty and ten surgical cases. For this first edition, a total of 39 healthcare workers were in attendance. The participants felt that the hands-on portion was very useful (56%) and wished to have more cases for more exposure. Comments from the plus/delta feedback emphasized on having in-person faculty rather than virtually. DISCUSSION AND CONCLUSION: The first edition of the EANS Vascular and Skull base Hands-on Neurosurgery Course in East Africa successfully run in Dar es Salaam. Subsequent editions should focus on more targeted in-person lectures better adapted to LMICs.
Keywords: Skull base; Neurovascular; Collaboration; Global neurosurgery; Training course